CUNINICO AND MAIPUCO TWO ARCHAEOLOGICAL SITES IN MARAÑÓN RIVER - Mac Kay Fulle, Martín (2009)
In the river Marañon, region Loreto, there are the archaeological places of Cuninico and Maipuco. Both places, given his context can give us a new idea of the importance and complexity of the existing pre-Columbian societies in the banks of Marañon and the adjacent gorges even already much brought in the XVIth century. While the registered materials give us information of the continuity in some even existing cultural events in the field of the communities of the ethnic group urarina.